(untitled) (Journal of the College of Basic Education, 2022)
Explained this study the effect of microwaves radiation with a frequency waves (a 2,450 MHz) on five fungal isolates (Aspergillus flavus, Aspergillus niger, Aspergillus fumigates, Penicillium chrysogenum, and alternaria alternate) .Fungal isolates that cultivated on the Sabouraud dextrose agar (SDA ) , at a rate of three frequency for each isolate fungi were exposed to the radiation of microwave oven with four time periods (0 second( control), 5 , 10 , 15 seconds). where the results showed highly growth of colonies of each fungal isolates used in the study that exposed to microwaves of time periods (5 seconds, 10 seconds). While killed all fungal colonies exposed to microwaves for the time period (15 seconds). This study proved the ability of the waves and microwaves period of time (15 seconds) and above to kill the fungal colonies and do not allow for the growth of fungal spores, meaning that the rate of growth of fungal colonies is inversely proportional to the length of time of exposure to radiation of microwaves